Engaging men as allies for a journey of gender transformation and improved nutrition - Verma, Avani; Bader, Nadine; Milcher, Susanne (Deutsche Gesellschaft für Internationale Zusammenarbeit, 2023)
The Indo–German Securing Nutrition, Enhancing Resilience (SENU) project implements a nutritionsensitive integrated approach linking nutrition education with government-supported community nutrition gardens. It aims at improving the dietary diversity of women (15–49 years) and young children (6–23 months) in six districts in Madhya Pradesh and Maharashtra. Through qualitative and quantitative social behavior change barrier and enabler analysis, SENU found that gender roles with respect to childcare and nutrition are hampering positive nutrition outcomes. Women are seen as responsible for household work, preparing food and childcare, but do not have the necessary decision-making power for their own and their small children’s nutrition. Based on the findings, SENU developed a gender-transformative strategy, which addresses attitudes and perceptions of gender roles and stereotypes at individual, family and community level. The nutrition education modules and tools have been revised to include participation opportunities for men and other household members and community meetings with innovative games for men. Further, through a campaign focusing on #MenCare, using participatory and community-based street theaters, the project promotes parents as a team and highlights their joint responsibility of childcare and nutrition. The project also focuses on economic empowerment and livelihood of women by mobilizing them in self-help groups to maintain community nutrition gardens for improved access and availability of nutritious food. These groups provide a peer-topeer network support, along with income generation through selling of surplus produce. SENU focuses on men as allies and women’s empowerment at the core, where men and other family members take an active role in family nutrition.